PENGARUH ENVIRONMENTAL REPORTING TERHADAP MARKET VALUE DENGAN CUSTOMER-RELATED PERFORMANCE SEBAGAI VARIABEL MEDIASI (Studi Empiris pada Perusahaan FMCG yang Terdaftar di BEI tahun 2019 – 2021) - Zadha Salsabila; Daljono Daljono (Diponegoro Journal of Accounting, 2023)
FMCG is said to be one of the largest contributors to environmental problems and global warming because of its close relationship with waste and other industrial pollution. While customers and shareholders play an important role in the success of FMCG businesses, their awareness of environmental issues is increasing but without being accompanied by the increase of corporates awareness of the importance of environmental reporting due to the lack of empirical evidence showing its effect on firm performance and market value. Using panel data components from 38 FMCG companies in Indonesia during 2019-2021 period, this study aims to examine the direct relationship between environmental reporting and market value as well as their indirect relationship through customer-related performance as mediator.Panel data regression analysis method with FEM (fixed effect model) and REM (random effect model) estimators was used to examine the relationship between environmental reporting, customer- related performance, and market value through two separate models. Furthermore, sobel test is used to test the role of customer-related performance as mediator.The results of this study showed a direct positive and significant effect of environmental reporting on market value as well as environmental reporting on customer-related performance. Meanwhile, customer-related performance was not shown to have a significant role in mediating the indirect relationship between environmental reporting and market value.